Access to justice and procedural speed with regard to letters rogatory in the recognition of foreign divorce judgments between Ecuador and Mexico following the breakdown of diplomatic relations - Flores Sisalima , Javier (2025)
This research analyzes whether the right of access to justice is violated by the ineffectiveness of letters rogatory in the process of homologating foreign divorce judgments between Ecuador and Mexico, particularly after the breakdown of diplomatic relations in 2024. The study was conducted using a mixed approach, with a descriptive and explanatory scope, using document review, interviews with family court judges, and surveys of legal professionals. The results reveal that, although access to justice is not formally limited, the principle of procedural speed is affected. This is because the processing of letters rogatory can take up to eight months, due to the complexity of the procedure, the overload of the judicial systems, and frequent errors in the documentation submitted. Likewise, a lack of training among some justice operators was found, which contributes to delays in the resolution of cases. It is concluded that the recognition of foreign divorce judgments is a valid and applicable procedure, but it requires adjustments to ensure its effectiveness. In this regard, it is recommended to strengthen electronic notification mechanisms and promote judicial training programs aimed at streamlining processes.